Arjen turvallisuus ja muuttoliikkeet - Assmuth, Laura; Haverinen, Ville-Samuli; Prokkola, Eeva-Kaisa; Pöllänen, Pirjo; Rannikko, Anni; Sotkasiira, Tiina (Tietolipas, 2021)
This book approaches contemporary migration to Finland from the perspective of everyday security, presenting an alternative view to theories that examine the links between migration and security from the perspective of securitisation. By treating everyday security as a theoretical concept and as empirical lived reality, the book foregrounds migrants' experiences of (in)security, as well as the perceptions of individuals and groups whose lives are touched by migration. Empirical studies investigate the ways in which security is produced at various levels, transnationally, and in multiple locations where encounters between long-term residents and newcomers occur, highlighting the roles of the welfare state, civic society, and the media. The book explores how everyday security is constructed between interdependent actors on personal, community and societal levels, concluding that the production of everyday security is a mutually beneficial, yet at times painstaking, process for all participants.